Development of Microsite-Based Digital Learning Media for Elementary English Instruction - Shanti Apriliyani; Taufiqulloh Taufiqulloh; Khusnul Khotimah (Jurnal Paedagogy, 2026)
This study aims to develop microsite-based digital learning media for English instruction in elementary schools. The research employed a Research and Development (R&D) method using the ADDIE model, limited to the analysis, design, and development stages. Data were collected through observations, interviews, questionnaires, and documentation. A limited trial was conducted in three elementary schools, involving three English teachers and 60 students who evaluated the practicality and usability of the developed microsite-based learning media. The research instruments included needs analysis forms, expert validation questionnaires for both material and media aspects, and response questionnaires for teachers and students. Data were analyzed using descriptive qualitative methods and simple quantitative analysis in the form of percentage scores. The findings indicate that the developed microsite-based digital learning media demonstrates a high level of feasibility, achieving average scores of 90% from material experts and 87% from media experts. Furthermore, the results of the limited user trials revealed very positive responses, with average practicality scores of 87% from teachers and 91.2% from students, placing the media in the “very practical” category. Therefore, the developed microsite-based digital learning media can be utilized as an effective alternative learning resource to support English instruction in elementary schools.